Feeling Beyond Words: Ineffability and Haptic Translational Praxis of Black German Writings - Adrienne N Merritt (Studies in 20th & 21st Century Literature, 2023)
In this article, I focus on selections from Black German essayistic and creative writings that center experiential knowledge that is personal and often multisensory. My case studies are excerpts from Farbe bekennen: Afro-deutsche Frauen auf den Spuren ihrer Geschichte (1986), its English translation by Anne V. Adams (Showing Our Colors 1992), and Natasha Kelly’s collection of interviews from her documentary film, Millis Erwachen (Milli’s Awakening) (2018), which Kelly herself translated. These texts, I argue, explore the ways in which words fail to fully express the visceral reaction of living while Black in Germany, particularly those that seek to make connections across geographic, linguistic, and generational differences. Focusing on the concept of transvivência (Araújo, Silva, and Silva-Reis) and hapticity of Black life (Tina Campt), I propose a model of translation that acknowledges the limitations of spoken and written words to convey all meaning and yet suggest that awareness through annotation, page format, and explanation might gesture toward more nuanced cultural references and ineffable experiences. Translation of Black-authored works into another language suggests a two-fold translation, from experience into language, from one language into another. I argue that hapticity combined with translation as transvivência has the ability to bridge what is felt and experienced with that which is read and observed. I conclude with a discussion of my own experience of translating Sharon Dodoa Otoo’s essay “Liebe” ‘Love’ from Eure Heimat ist unser Albtraum (Your Homeland is Our Nightmare).
Keywords: Black German studies; Black diaspora; Translation